Developing E-LKPD for Junior High School Students : Enhancing Explanatory Text Writing Skills with Liveworksheets Support - Sari, Evi Merita; Assidik, Gallant Karunia (Jurnal Paedagogy, 2025)
This study aims to develop interactive LKPD based on Liveworksheets to improve Indonesian language learning outcomes in explanatory text material. This study involved 31 students of class IX C of SMP Muhammadiyah Al-Kautsar PK Kartasura, by implementing the research and development (R&D) method using the ADDIE model. The instruments used in this study consisted of several types to collect data that support the development and validation of interactive E-LKPD assisted by Liveworksheets. The data collection process was carried out by delivering material in the form of PPT which aims to explain the explanatory text material. After that, students worked on the E-LKPD questions that were already available on Liveworksheets. The data sources in this study were obtained from validators who were material experts, media experts, language experts, and students of class IX C of SMP Muhammadiyah Al-Kautsar PK Kartasura. The validation results showed that the material aspect obtained a percentage of 84%, while the media aspect reached 85% and the language aspect reached 82%. To measure the effectiveness of the media, a comparison of the results of the pre-test and post-test of students was conducted, with an average post-test score of 90.32 and a completion rate of 95%. Based on these findings, it can be concluded that interactive LKPD based on Liveworksheets is a learning media that is suitable for use.